Evaluation of Open-Source Upper Limb Prostheses Models for 3D Printing: Grasping Performance Using Silicone Fingertips Covers - Tobaro, Erica Tiemi [UNESP]; Manero, Albert; Senthil, Pavan; Vishanagra, Om; Paschorelli, Luis Carlos [UNESP]; Sparkman, John; Sandnes, Frode Eika; Medola, Fausto Orsi [UNESP] (Springer Nature, 2025)
Many upper limb prostheses are heavy, difficult to control, and have limited functions. This often leads to device abandonment. The use of 3D printing in assistive devices has enabled customization and personalization, providing greater precision, comfort, and user satisfaction while reducing abandonment. However, there is still limited information regarding the mechanical specifications of models used for 3D-printed prostheses, such as evidence on functional performance, durability, need for reprints, comfort and limits of use. This research aimed to evaluate the functional performance of open-source 3D-printed prostheses, contributing to a better understanding of factors that may influence their performance, such as the use of silicone fingertip covers. The study assessed three open-source prosthesis models: the Kwawu Arm Thermoformed Version, the Kwawu Arm Socket Version, and the Unlimbited Arm. Their performance was evaluated based on the ability to hold 31 objects of various shapes and weights for 60 s through three attempts. Although the prostheses demonstrated functionality for handling objects, relatively high failure rates were observed across all three models. Considering that the objects are common everyday items, users may face challenges or even an inability to handle certain objects in practical scenarios. The results revealed a significant performance improvement with the use of silicone fingertip covers, with increases of approximately 20%. These findings provide insights into the development of the development design process of new prosthesis models and highlight the importance of continued research into the performance of mechanical prostheses developed using 3D printing based on open-source models.